Reasoned opinion on the modification of the existing MRLs for pendimethalin in various crops. (3rd April 2014) - ,
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, Belgium compiled an application to raise the existing MRLs for the active substance pendimethalin on swedes, turnips and salsify and Germany received an application from BASF SE to raise the existing MRLs for pendimethalin on carrots, horseradish, parsnips, parsley root, salsify, chicory root, spices (roots or rhizome), whereas no amendment of the exiting MRL on celeriac was proposed. The evaluating Member States Belgium and Germany drafted evaluation reports in accordance with Article 8 of Regulation (EC) No 396/2005 which were submitted to the European Commission and forwarded to EFSA. According to EFSA the data are sufficient to propose a MRL of 0.7 mg/kg for carrots, horseradish, parsnips, parsley root and salsify and 0.2 mg/kg for celeriac. Tentative MRLs of 0.4 mg/kg for swedes and turnips and 0.2 mg/kg for chicory roots were derived by applying the proportionality approach. The extrapolation of the MRL of 0.5 mg/kg set for the group of herbal infusions (roots) to the group of spices (roots or rhizome) is acceptable under certain conditions. For horseradish which is classified in the group of spices/roots or rhizome (code 840040), the MRL should be aligned with the MRL derived for fresh horseradish vegetables (code 213040) using an appropriate dehydration factor. Based on the risk assessment results, EFSA concludes that the intended uses of pendimethalin on the crops under consideration will not result in a consumer exposure exceeding the toxicological reference value and therefore are unlikely to pose a consumer health risk.